On the Stability of Research Joint Ventures: Implications for Collusion - Jo Seldeslachts; Tomaso Duso; Enrico Pennings (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
Though there is a body of theoretical literature on research joint ventures (RJV) participation facilitating collusion, empirical tests are rare. Even more so, there are few empirical tests on the general theme of collusion. This note tries to fill this gap by assuming a correspondence between the stability of research joint ventures and collusion. By using data from the US Nation Cooperation Research Act, we show that large RJVs in concentrated industries are more stable and hence more suspect to collusion.
urn:nbn:de:bvb:19-epub-13312-2
Keywords: L24; L44; L52; 330; research joint ventures; product market collusion; empirical test